Prevalence of headaches in football players - Sallis, R. E.; Jones, K. (Medicine & Science in Sports & Exercise, 2000)
BACKGROUND: Football coaches and team physicians rely heavily on players' reports of symptoms in deciding whether a player may return to the game after sustaining head trauma. The decision is made difficult by the wide variety of associated symptoms, some of which (e.g., headache is among the most common) may or may not be associated with serious head injury. More information is needed about the clinical significance of football-related headache. METHODS: To assess the frequency of headache associated with playing football, we analyzed responses to our questionnaire asking about incidence, frequency, and outcome of football-related headache from 443 football players (320 from college, 123 from high school). RESULTS: Eighty-five percent of respondents reported previous headache related to hitting in football. Asked specifically about their most recent game, 21% of respondents reported having had headache during that game. Of players who had headache, only 19% informed the team physician, trainer, or coach, and only 6% were removed from the game. Twenty-seven percent of respondents reported previous diagnosis of cerebral concussion by medical personnel. Defensive backs (25%), defensive linemen (19%), and offensive linemen (18%) were most likely to have headache, related to hitting. CONCLUSIONS: Our data confirm that posttraumatic headache is commonly associated with football participation and often goes unreported. Given that the most serious complications of head injuries (e.g., second-impact syndrome) occur infrequently, headache as an isolated symptom lacks specificity in predicting such complications in football players. Therefore, unless it persists or is accompanied by additional symptoms, headache alone may not reliably suggest the need to remove players from the game.